Construction and Operation of a High-Speed, High-Precision Eye Tracker for Tight Stimulus Synchronization and Real-Time Gaze Monitoring in Human and Animal Subjects - Farivar, Reza; Michaud-Landry, Danny (Frontiers in Systems Neuroscience, 2016)
Measurements of the fast and precise movements of the eye—critical to many vision, oculomotor, and animal behaviour studies—can be made non-invasively by video oculography. The protocol here describes the construction and operation of a research-grade video oculography system with 0.1° precision over the full typical viewing range at over 450Hz with tight synchronization with stimulus onset. The protocol consists of three stages: (1) system assembly, (2) calibration for both cooperative and for minimally cooperative subjects (e.g., animals or infants), and (3) gaze monitoring and recording.